Implementation of Corporate Social Responsibility By Companies To Establish Corporate Existence In Society (A Review From Business and Legal Norm Perspectives) - Aris Yulia; Fatma Ayu Jati Putri (International Journal Labs, 2025)
Corporate Social Responsibility (CSR) emerged as a prominent concept in the 1990s, garnering attention from academics, non-governmental organizations (NGOs), and business practitioners. Initially, CSR focused on corporate accountability to shareholders but later expanded to include broader responsibilities to stakeholders, such as employees, consumers, suppliers, communities, and environmental constituents. In Indonesia, the legal framework for CSR is established under Law Number 25 of 2007 on Investment and Law Number 40 of 2007 on Limited Liability Companies, transforming CSR from a moral obligation into a legal mandate. This shift has sparked debates concerning the conceptual and practical aspects of CSR. However, fulfilling CSR obligations, both legal and social, positively impacts a company's existence in society. Companies adhering to these obligations are perceived more favorably, enhancing their corporate image and long-term sustainability. This study examines the implementation of CSR through the lens of business ethics and legal norms, highlighting its role in reinforcing corporate existence in the community.